Broad Spectrum Antiviral Agent Niclosamide and Its Therapeutic Potential - Xu, Jimin; Shi, Pei-Yong; Li, Hongmin; Zhou, Jia (ACS infectious diseases, 2020)
The recent outbreak of coronavirus disease 2019 (COVID-19) highlights an urgent need for therapeutics. Through a series of drug repurposing screening campaigns, niclosamide, an FDA-approved anthelminthic drug, was found to be effective against various viral infections with nanomolar to micromolar potency such as SARS-CoV, MERS-CoV, ZIKV, HCV, and human adenovirus, indicating its potential as an antiviral agent. In this brief review, we summarize the broad antiviral activity of niclosamide and highlight its potential clinical use in the treatment of COVID-19.